PEMBATASAN MASA JABATAN KEPALA DAERAH DI NEGARA REPUBLIK INDONESIA - Mohammad Ilham Agang (Borneo Law Review, 2018)
In accordance with legal issues that have been defined, the findings of this research are (1) the term of office of the head of the region should be limited so that the head region can carry out their duties and functions well as mandated in legislation. It also to prevent abuse of authority; (2) The principle of term limits of heads of regions in Indonesia within the framework of the democratic constitutional state in achieving good governance is that the position of head of the region is limited by time, the substance of the authority and the place or location. In order to run a good political education and consider the moral aspects, the head of region post should be clearly limited in term of its period. (3) The law setting of term limit of head of region in Indonesia under article 7 letters N and O of act number 8 of 2015 concerning election of governors, regents, and mayors clearly noted that they never serve yet as governor, regent and mayor for two period at the same position. The law is very clear that the head and deputy head of the region can only serve two times period and thereafter cannot be re-elected because it is at risk to misuse the authority and tend to perform acts of maladministration. Based on the findings above, this dissertation suggests at least three points (1) the term of office of the head of the region should be limited so that the head region can carry out their duties and functions well as mandated in legislation. It also to prevent abuse of authority; (2) The principle of term limits of heads of regions in Indonesia should be clarified in detail to prevent multiple interpretations among people that ultimately lead to polemic that may interfere the Indonesian government performance. (3) There must be clear legal sanctions against the head of region candidate who violates the requirements to run for election as the head of the region based on Law No. 8 of 2015 concerning Election of governors, regents, and mayors.